Further Assessment of Meyer and Allen's Three-Component Model of Organizational Commitment: Croatian Data - Maslić-Seršić, Darja (Array, 1999)
Meyer and Allen (Allen & Meyer, 1990; Meyer & Allen, 1991) proposed a three-component model of organizational commitment that integrated a variety of alternative conceptualizations. They identified affective, normative, and continuance commitment as elements comprising a three-component conceptualization of organizational commitment. According to their model, an employee simultaneously experiences commitments to the organization that are based on emotional attachment (affective commitment), a feeling of obligation to the organization (normative commitment), and perceptions of the costs of leaving the organization (continuance commitment). Using measures of the component constructs developed by Meyer and Allen (1984) and Allen and Meyer (1990), researches have explored - and mostly confirmed - differences in the antecedents and consequences of the component constructs. This study evaluates Meyer and Allen model of commitment in Croatian society, and deals with the cross-cultural applicability of developed scales. Subjects (N=806) were professionals from 22 industrial organizations that employed among 200 and 1000 employees. A group of 70 high educated job applicants from different organizations were also included in the study.